A legal policy analysis: the current and prospective regulatory framework for renewable energy and energy efficiency in Egypt - Abulzahab, Karam J. (AUC Knowledge Fountain, 2010)
Egypt has excellent natural conditions for the generation of electricity from Renewable Energy (RE) sources. It has in particular an immense potential for solar and wind energy. At the same time, an Egyptian energy crisis is emerging. Conventional domestic energy sources are declining and thus, Egypt will have to rely increasingly on costly imported energy in the near future. In addition, energy efficient (EE) consumption is an almost unknown term within the Egyptian society. Experts project for Egypt an energy saving potential of approximately 70%. Therefore, the promotion of RE & EE could be a successful policy instrument to mitigate the emerging Egyptian energy crisis. Furthermore, the development of a green Egyptian economy based on RE & EE could contribute to the countryÂ´s economic growth by increasing foreign direct investment, creating employment and providing much needed technology transfer. Besides these political considerations, Egypt could also fulfill its international obligation under the United Nation Framework Convention on Climate Change (UNFCCC) to mitigate the adverse effects of climate change by promoting RE & EE. Key to the sustainable diffusion of RE & EE and the eventual creation of a green domestic economy is the implementation of a sound and consistent legal policy. The Egyptian regulator has already identified this need and has implemented a series of regulatory measures to promote RE & EE. In the field of RE, it is the declared objective of the Egyptian government to satisfy 20% of the country's primary energy demand through RE by 2020. In order to reach this ambitious goal, Egypt is implementing a tendering system to award RE projects to private developers. However, it is the long-term objective to regulate the Egyptian RE sector through a feed-in law. For the promotion of EE, the Egyptian government has not yet formulated an official policy. Nevertheless, it has developed EE Building Codes, EE standards and labels for electric appliances, and it has promoted solar water heating systems. Unfortunately, these efforts have not yet led to the creation of a substantial RE & EE sector in Egypt. In general, the reason for this failure is that the Egyptian RE & EE strategy lacks comprehensiveness as well as consistent long-term dedication. Invitations to tender usually focus entirely on wind energy projects, while neglecting the huge potential for solar energy. Legal and price uncertainties further impede the promotion of RE. The Egyptian approach to promote EE is highly fragmented and incoherent, and suffers from lack of enforcement and acceptance in the market. However, existing subsidies for conventional energy sources and unfavorable electricity pricing structures for RE & EE remain the key barriers to the sustainable development of the sector. Although there are many regulatory instruments to minimize the aforementioned barriers, only consistent long-term commitment by the Egyptian government can lead to the establishment of healthy domestic RE & EE industry.